Exploring scientific legitimacy of orthorexia nervosa: a newly emerging eating disorder - Chaki, B.; Pal, S.; Bandyopadhyay, A. (Journal of Human Sport & Exercise, 2013)
Eating disorders are a range maladaptive eating behaviours characterized by highly restrictive and unhealthy food intake patterns that lead to variety of psychiatric, physiological and health complications such as depression, anxiety, and personality disorders etc. Many of these psychological eating disorders such as anorexia nervosa or bulimia nervosa have been recognized as disease by the Diagnostic and Statistical Manual of Mental Disorders (DSM IV) of American psychiatric association. However there are many newly identified eating disorders which are yet to be recognized as disease by American psychiatric association. Orthorexia nervosa (ON) is one such unrecognized psychological eating disorder in which the person becomes obsessed with eating pure, healthy and right kinds of foods to improve health. There are no standard diagnostic criteria for ON and in recent times different researchers used different questionnaire to assess the presence of orthorexic characters. Many researchers have raised questions about the validity of ON as a unique disorder and many of them preferred to describe ON as a variant of existing eating or anxiety disorder. On the other hand many researchers believe that ON is an unique eating disorder different from other recognized eating disorders and it should be recognized as a disease in the planned fifth edition of the American Psychiatric Association's (APA) Diagnostic and Statistical Manual of Mental Disorders (DSM 5), due to be published in 2013. The review aims to highlight the present understanding about ON including its character, physiological and psychological consequences and different diagnostic features used by different researchers to evaluate ON. The review will compare ON with other recognized eating disorders, and assess the scientific validity of ON to be considered as a valid psychological eating disorder by American Psychiatric Association's (APA).